1988
DOI: 10.1017/s0033291700008291
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal eating attitudes in London schoolgirls — a prospective epidemiological study: factors associated with abnormal response on screening questionnaires

Abstract: SynopsisOne thousand and ten unselected London state schoolgirls were screened by questionnaire to identify an ‘at risk’ cohort displaying abnormal eating attitudes and two control cohorts, one with probable general psychiatric morbidity, one without. Members of all cohorts were assessed at interview for the presence of eating disorder and for putative risk factors implicated in the development of anorexia nervosa. A prevalence rate of 0·99 % was detected for clinical eating disorder and 1·78 % for the partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
5

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(90 citation statements)
references
References 11 publications
7
78
5
Order By: Relevance
“…The prevalence of eating problems among female adolescents based on EAT scores has been reported to vary from 5% to 22% in adolescent female populations in Europe and North America (Button & Whitehouse, 1981;Mann et al, 1983;Cooper, Waterman, & Fairburn, 1984;Lichener, Arnett, Rallo, Srikameswaran, & Vulcano, 1986;Johnson-Sabine, Wood, Patton, Mann, & Wakeling, 1988;Lachenmeyer & Muni-Brander, 1988;Whitaker et al, 1989;Patton, Johnson-Sabine, Wood, Mann, & Wakeling, 1990;Wichstrøm, 1995;Dancyger & Garfinkel, 1995). Nasser (1986) reported prevalence rates of 22% and 12%, respectively, among Arab students living in London and Cairo.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of eating problems among female adolescents based on EAT scores has been reported to vary from 5% to 22% in adolescent female populations in Europe and North America (Button & Whitehouse, 1981;Mann et al, 1983;Cooper, Waterman, & Fairburn, 1984;Lichener, Arnett, Rallo, Srikameswaran, & Vulcano, 1986;Johnson-Sabine, Wood, Patton, Mann, & Wakeling, 1988;Lachenmeyer & Muni-Brander, 1988;Whitaker et al, 1989;Patton, Johnson-Sabine, Wood, Mann, & Wakeling, 1990;Wichstrøm, 1995;Dancyger & Garfinkel, 1995). Nasser (1986) reported prevalence rates of 22% and 12%, respectively, among Arab students living in London and Cairo.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with these concerns and behaviors have been found to be at risk of developing an eating disorder (Allgood-Merton, Lewinsohn, & Hops, 1990;Brooks-Gunn, 1988;Herzog, Hopkins, & Burns, 1993;Johnson-Sabine, Wood, Patton, & Mann, 1988;Killen et al, 1994;Patton, Johnson-Sabine, Wood, Mann, & Wakeling, 1990;Rierdan, Koff, & Stubbs, 1988;Taylor et al, in press). …”
Section: Student Bodies Softwarementioning
confidence: 99%
“…The first published studies employing a two-stage survey on teenage girls had two common outcomes: 1) a reduction in the number in detected cases of AN, and 2) the frequent corroboration of partial AN syndrome, compared to studies using treatment-seeking samples. In fact, several surveys did not identify any anorexic participants from among the study participants (Jonhson-Sabine et al, 1988;Mann et al, 1983;Patton et al, 1990), as shown table 4 (see Appendix). Subsequent double-stage prevalence studies, with identification of false negatives, have shown higher prevalence rates.…”
Section: Two-and Three-stage Surveymentioning
confidence: 98%